STRATEGI PEMBELAJARAN DALAM PERSPEKTIF AL-QUR’AN - Muntafi, Ahmad Zaki; Majid, Aditya Syahrul (STAI Al-Aqidah Al-Hasyimiyyah, 2019)
Education in the process is inseparable with the supporting instruments in it. This instrument is quite important because it is vital for the ongoing educational process. The absence of this instrument certainly has a negative impact on the education process, especially for the learning process. The existence of an appropriate learning model will have a significant impact, and vice versa. Learning strategis become an altenative in compiling the learning process. For the education process, this learning strategy becomes an important reference. Meanwhile, for Islamic education, this learning strategy must be seen in the perspective of the Koran, where the Koran becomes theological footing in religion. Furthermore, learning strategies that are based on the existence of the Koran, are expected to be able to give birth to spiritual ideals that are in it.